OPTIMASI PROSES PRODUKSI UNTUK PRODUK MAKANAN DENGAN METODE INTEGER LINEAR PROGRAMMING (ILP) PADA PT PSA - Abbas, Bahtiar S.; Indriani, Wiwi (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
PT PSA in its 16 months of operations do not have a structured production planning, beside that material planning and management is conducted based on intuition. Based on these conditions, this study aims to create a global production image to maximize profit, and material planning and management for the June 2008 period. The integer linear programming method is used due to the integer unit characteristics of the final product; thereby the optimization results should also be in in integer. The optimum results from the profit maximization problem is Rp 968,184,500.00 derived from production of 11058 balado crisps boxes, 19455 cheese crisps boxes, 16636 pea boxes and 13166 pilus boxes. From the profit maximization problem results, it is concluded that the resource capacity of PT PSA is enough to fulfill production plan for the June 2009 period.